2017
DOI: 10.1007/s00029-017-0314-x
|View full text |Cite
|
Sign up to set email alerts
|

A class of knots with simple SU(2)-representations

Abstract: We call a knot in the 3-sphere SU (2)-simple if all representations of the fundamental group of its complement which map a meridian to a tracefree element in SU (2) are binary dihedral. This is a generalization of being a 2-bridge knot. Pretzel knots with bridge number ≥ 3 are not SU (2)-simple. We provide an infinite family of knots K with bridge number ≥ 3 which are SU (2)-simple.One expects the instanton knot Floer homology I (K) of a SU (2)-simple knot to be as small as it can be -of rank equal to the knot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…In [17], Zentner studied knots with the property that all of its SU (2) representations are binary dihedral and called such knots "SU (2)-simple". He showed that if a knot K is SU (2)-simple and satisfies a certain genericity hypothesis, then the higher differentials on the instanton complex vanish.…”
Section: Figurementioning
confidence: 99%
“…In [17], Zentner studied knots with the property that all of its SU (2) representations are binary dihedral and called such knots "SU (2)-simple". He showed that if a knot K is SU (2)-simple and satisfies a certain genericity hypothesis, then the higher differentials on the instanton complex vanish.…”
Section: Figurementioning
confidence: 99%
“…Example 2.6. The manifold Y (T 2,3 , T 2,−3 ) is the branched double cover of 8 17 (see [Zen17,§5]), which has unknotting number 1. One can check that this SU(2)-cyclic manifold is 37 2 -surgery on the (−2, 3, 7)-pretzel knot, which will appear in Theorem 3.1 as the mirror of the knot k(2, 2, 0, 0).…”
Section: Some Su(2)-cyclic Graph Manifoldsmentioning
confidence: 99%
“…We know very little about the remaining case, namely hyperbolic manifolds, but we can prove that some closed hyperbolic 3-manifolds are SU(2)-cyclic by the following, which was claimed without proof in [Zen17] and builds on work of Cornwell [Cor15].…”
Section: Introductionmentioning
confidence: 98%